Diversification of the widespread neotropical frog Physalaemus cuvieri in response to Neogene-Quaternary geological events and climate dynamics - Oliveira Miranda, Nubia Esther de; Maciel, Natan Medeiros; Lima-Ribeiro, Matheus Souza; Colli, Guarino Rinaldi; Baptista Haddade, Celio Fernando [UNESP]; Collevatti, Rosane Garcia (Elsevier B.V., 2019)
Here we reconstructed the demographical history and the dispersal dynamics of Physalemus cuvieri through the Neogene-Quaternary periods by coupling DNA regions with different mutation rates, ecological niche modelling, reconstruction of spatio-temporal lineage dispersal and coalescent simulations. Still, to test alternative diversification scenarios we used approximate Bayesian computation. Molecular phylogenetic analysis recovered four deep and strongly supported clades, which we interpret as population lineages. The ancestral location reconstruction placed the root in southcentral Amazonia, and the dispersal events indicate that spatial displacement was widespread early in the diversification of this species. The demographical scenario of Multiple Refugia with recent lineage admixture was the most likely hypothesis to predict the observed genetic parameters of P. cuvieri. Our results revealed that Neogene orogenic events might have played a prominent role in the early diversification of P. cuvieri. The species shows deep divergences with strong regional population structure, despite its widespread distribution. Final uplift of the central Brazilian Plateau and formation of the river basins in Central South America played an important role in the origin, diversification and the maintenance of P. cuvieri lineages.
Keywords: Anura; Dispersal dynamics; Ecological niche modelling; Genetic diversity; Leptodactylidae; Phylogeography